Culturable marine fungal biodiversity from the south coast of Jember, East Java, Indonesia - ENDAH PUSPITASARI; KARTIKA SENJARINI; I DEWA AYU RATNA DEWANTI; VIRLIANA FEBRIANTI; FITRIANTI MILHATUL HASANAH; ANTJE LABES (Society for Indonesian Biodiversity, 2025)
Abstract. Puspitasari E, Senjarini K, Dewanti IDAR, Febrianti V, Hasanah FM, Labes A. 2025. Culturable marine fungal biodiversity from the south coast of Jember, East Java, Indonesia. Biodiversitas 26: 3000-3010. Marine fungi with their unique environment are a promising source for drug discovery. Their distinct natural products, different from those of terrestrial fungi, give them potential bioactivity. However, not all marine fungi are culturable. This research aimed to determine the biodiversity of culturable marine fungi from Jember south coast, East Java, Indonesia. The sampling was conducted on samples available on the Jember south coast, East Java, Indonesia, including seawater, sand, wood remains, green algae, and red algae. The isolation of marine fungi using fungal basal media. Once a single colony with different morphotypes was obtained, it was characterized based on its morphology (macroscopically and microscopically using bright field and scanning electron microscope) and molecularly. The fungal morphological features were described based on the colony’s and cell’s appearance. The molecular characteristics were carried out using DNA barcoding based on the internal transcribed spacer. The results revealed 17 isolates of culturable marine fungi from Jember south coast. They were dominated by the genus Penicillium (47.059%), followed by Scopulariopsis and Curvularia (17.647%), Aspergillus (11.765%), and Cladosporium (5.882%); members of phylum Ascomycota. The results showcase the rich diversity of species that have potential as drug candidates. Further studies are needed to reveal their bioactivity.